Stimulation of Acanthamoeba castellanii excystment by enzyme treatment and consequences on trophozoite growth - Fechtali-Moute, Zineb; Loiseau, Philippe M.; Pomel, Sébastien (Frontiers in Cell and Developmental Biology, 2022)
Acanthamoeba castellanii is a widespread Free-Living Amoeba (FLA) that can cause severe ocular or cerebral infections in immunocompetent and immunocompromised patients, respectively, besides its capacity to transport diverse pathogens. During their life cycle, FLA can alternate between a vegetative form, called a trophozoite, and a latent and resistant form, called a cyst. This resistant form is characterized by the presence of a cell wall containing two layers, namely the ectocyst and the endocyst, mainly composed of cellulose and proteins. In the present work, we aimed to stimulate Acanthamoeba castellanii excystment by treating their cysts with a cellulolytic enzyme, i.e. cellulase, or two proteolytic enzymes, i.e. collagenase and pepsin. While 11 days were necessary to obtain total excystment in the control at 27°C, only 48 h were sufficient at the same temperature to obtain 100 % trophozoites in the presence of 25 U/mL cellulase, 50 U/mL collagenase or 100 U/mL pepsin. Additionally, more than 96 % amoebae have excysted after only 24 h with 7.5 U/mL cellulase at 30°C. Nevertheless, no effect of the three enzymes was observed on the excystment of Balamuthia mandrillaris and Vermamoeba vermiformis. Surprisingly, A. castellanii trophozoites excysted in the presence of cellulase displayed a markedly shorter doubling time at 7 h, in comparison to the control at 23 h. Likewise, trophozoites doubled their population in 9 h when both cellulose and cellulase were added to the medium, indicating that Acanthamoeba cyst wall degradation products promote their trophozoite proliferation. The analysis of cysts in epifluorescent microscopy using FITC-lectins and in electron microscopy revealed a disorganized endocyst and a reduction of the intercystic space area after cellulase treatment, implying that these cellular events are preliminary to trophozoite release during excystment. Further studies would be necessary to determine the signaling pathways involved during this amoebal differentiation process to identify new therapeutic targets for the development of anti-acanthamoebal drugs.